Mercury risks versus nutritional benefits of tribal commercial fish harvests in the Upper Laurentian Great Lakes. Issue 4 (18th May 2016) - Dellinger, Matthew J.; Ripley, Michael P.
ABSTRACT: The Inter-Tribal Fisheries and Assessment Program (ITFAP) of the Chippewa Ottawa Resource Authority (CORA) in Sault Ste. Marie, Michigan, has been monitoring contaminant concentrations in the fillet portions of lake trout ( Salvelinus namaycush ) and lake whitefish ( Coregonus clupeaformis ) from the waters of lakes Superior, Huron, and Michigan since 1991. The primary purpose of this article is to present a risk quantification of methylmercury (MeHg) that is adjusted for nutritional benefit, originally presented by Ginsberg and Toal (2009, 2015) on trends in contaminant concentrations in fillet portions of these commercial fish that we recently reported in Dellinger et al. (2014 ). Both species of fish caught by tribal fishermen showed clear benefits to cardiovascular health and infant neurodevelopment if consumed at a rate of six ounces per week. However, other popularly consumed fish such as cod, tuna, and tilapia are estimated to have only marginal benefit or net negative effects on cardiovascular health and infant neurodevelopment. This dynamic assessment of benefits and risks further demonstrates the importance of traditionally caught fish in tribal health.